2020
DOI: 10.1142/s2424835520500514
|View full text |Cite|
|
Sign up to set email alerts
|

Range of Motion Following Extensor Tendon Splitting vs. Tendon Sparing Approaches for Plate Osteosynthesis of Proximal Phalangeal Fractures – A Systematic Review and Meta-Analysis

Abstract: Background: Several approaches to plate fixation of the proximal phalanx have been proposed, such as the dorsal extensor splitting approach and the lateral or dorso-lateral extensor sparing approach, which aims to minimise invasiveness to promote native extensor tendon glide. This study aimed to meta-analyse the outcomes of these two approaches. Methods: A systematic review of electronic databases was undertaken, and the outcomes of comparative studies meta-analysed. Results: Three studies were included for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…6,32 A recent meta-analysis by Sivakumar (yet to be published) compared extensor sparing lateral plating to tendon-splitting dorsal plating and found an statistically significant difference of 8.6° greater range with lateral plating. 33 All included studies demonstrated inferior TAM to that calculated here. A major complication rate of between 3.6% and 6% also compares favorably to other techniques.…”
Section: Discussioncontrasting
confidence: 50%
“…6,32 A recent meta-analysis by Sivakumar (yet to be published) compared extensor sparing lateral plating to tendon-splitting dorsal plating and found an statistically significant difference of 8.6° greater range with lateral plating. 33 All included studies demonstrated inferior TAM to that calculated here. A major complication rate of between 3.6% and 6% also compares favorably to other techniques.…”
Section: Discussioncontrasting
confidence: 50%
“…It is now well accepted that rigid fixation constructs confer significantly improved outcomes when compared to non-rigid constructs, as they facilitate precise alignment and earlier mobilization. 4,11,12 Biomechanical and clinical studies utilizing comminuted phalangeal models indicate that open reduction with plate fixation affords superior stability when compared to closed reduction and k-wire stabilization. [13][14][15] Lower profile and variable angle locking plates (which preserve periosteal vascularity whilst evenly distributing load across all screws) have further improved outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although many of these fractures can be treated non‐operatively, factors such as patient characteristics, the mechanism of injury and fracture configuration may mandate surgical intervention. There have been a number of surgical advances in the management of metacarpal and phalangeal fractures since the turn of the century, including minimally invasive approaches that aim to diminish soft tissue disruption, the development of lower profile plating systems and a focus on immediate postoperative mobilization 4–7 . However, little information is available on the changes in outcome and practice rendered by these developments.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the reduction in bulkiness of hardware implants with the use of low-profile minifragment plates or with a different lateral/midlateral/tendon sparing approach, the postoperative final ROM has not been significantly improved. 3,4 We thus suggest that the key factor is not solely the use of a volar or midlateral approach as with a volar or lateral or dorsolateral position of the plate, tendon adhesions still occur. On the contrary, the key issue is represented by the presence or absence of vascularized gliding tissue that works as a barrier preventing tendon adhesions in the interface of the tendon plate.…”
Section: Dear Editormentioning
confidence: 95%
“…Despite the reduction in bulkiness of hardware implants with the use of low-profile mini-fragment plates or with a different lateral/midlateral/tendon sparing approach, the postoperative final ROM has not been significantly improved. 3,4…”
mentioning
confidence: 99%